If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-2x + 5) = 9 Reorder the terms: 3(5 + -2x) = 9 (5 * 3 + -2x * 3) = 9 (15 + -6x) = 9 Solving 15 + -6x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -6x = 9 + -15 Combine like terms: 15 + -15 = 0 0 + -6x = 9 + -15 -6x = 9 + -15 Combine like terms: 9 + -15 = -6 -6x = -6 Divide each side by '-6'. x = 1 Simplifying x = 1
| 1x+.5y=6 | | 21=7y+7+(y+3) | | 7(-6x+1)=-329 | | X-2(x+3)=-2(x+1)-4 | | 2x+1+3x=30 | | x=a(a-b)+b(a+b) | | x=-3+13 | | 2x-3+19=17 | | 5x=63.25 | | [2x+3]=-5 | | 7(-1x+5)=-7 | | x^2-2+3x+8=180 | | -8y=48-4y | | 7.1x+4.4-2x-8.7= | | -7(2x+4)=-70 | | [8x+5]=21 | | 72-10x=12 | | -6x+2=3x-79 | | [4x-8]=20 | | x+4=-20-x | | 6x-3=-7x-133 | | 4-3x+2x=-18+2 | | 6=16-13d | | -140=4x-6(-x+10) | | 5y=-2x-15 | | 10x^2-42x+44=0 | | 5x+13=35+7x | | -1-2x-6x=-65 | | 5x-4=30x+16 | | 6x-4(2-x)=14 | | -17=-2x-2x-5 | | 2=8x-32 |